Shenqi Fuzheng Injection Reverses Cisplatin Resistance through Mitofusin-2-Mediated Cell Cycle Arrest and Apoptosis in A549/DDP Cells - Xiong, Ying (Evid Based Complement Alternat Med, 2018)
The goal of this evaluation was to examine the mechanisms of Shenqi Fuzheng injection (SFI), an extract made from the plants Radix Astragali and Radix Codonopsis, in the process of chemotherapy sensitivity in non-small-cell lung cancer (NSCLC) cells. We investigated the expression of mitofusin-2 (Mfn2), a mitochondrial GTPase that may be related to chemoresistance, and found that Mfn2 expression was lower in human cisplatin-resistant lung carcinoma A549/DDP cells than in cisplatin-susceptible A549 cells. Chemosensitivity to cisplatin was restored in A549/DDP cells following supplementation in conjunction with SFI treatment, the effect of which we evaluated via cell cycle, apoptosis, and cell signaling analysis. We found that the combined use of A549/DDP cells with SFI and cisplatin enhanced cell cycle arrested in the G(2)/M phase, which was accompanied by upregulation of p53 and p21 protein expression and induced mitochondrial apoptosis in conjunction with the upregulation of Bax and the downregulation of Bcl-2 protein expression. Moreover, cell cycle arrest and mitochondrial apoptosis coincided with the upregulation of Mfn2 expression, which, in turn, was related to the increased mitochondrial membrane permeabilization and elevated reactive oxygen species. In summary, our findings suggest that the effect of SFI in increasing chemotherapy sensitivity in cisplatin resistance of NSCLCs occurs through cell cycle arrest and the initiation of mitochondrial apoptosis involved in the upregulation of Mfn2 expression.